Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s00784-016-1884-2
|View full text |Cite
|
Sign up to set email alerts
|

Presence of plaque, gingivitis and caries in Sudanese children with congenital heart defects

Abstract: ObjectivesThe objective of this study is to assess the presence of plaque, gingivitis, and caries in a group of Sudanese children with congenital heart defects CHDs (cases) and compare them to children without CHDs (controls).Materials and methodsThis analytical cross-sectional study included cases (N = 111, with a mean age of 7.2 ± 3.0 years) and controls (N = 182, with a mean age of 7.2 ± 2.8 years) from Khartoum, Sudan. Examinations were done by two calibrated dentists using plaque index, gingival index, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
57
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(78 citation statements)
references
References 31 publications
9
57
1
Order By: Relevance
“…A total number of 120 children from Khartoum city were enrolled in this study: 60 with CHD (CHD cases) and 60 controls (Ahmed Gasim cardiac Centre for CHD cases and schools and kindergartens for the controls). Details regarding the setting, sampling and study design were previously reported (Ali et al, 2016). Children with confirmed diagnosis with a CHD in the age group 3–12 years were included, but critically ill children and those using medications other than for CHDs were excluded (Ali et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total number of 120 children from Khartoum city were enrolled in this study: 60 with CHD (CHD cases) and 60 controls (Ahmed Gasim cardiac Centre for CHD cases and schools and kindergartens for the controls). Details regarding the setting, sampling and study design were previously reported (Ali et al, 2016). Children with confirmed diagnosis with a CHD in the age group 3–12 years were included, but critically ill children and those using medications other than for CHDs were excluded (Ali et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Details regarding the setting, sampling and study design were previously reported (Ali et al, 2016). Children with confirmed diagnosis with a CHD in the age group 3–12 years were included, but critically ill children and those using medications other than for CHDs were excluded (Ali et al, 2016). Data collection was done in 2011 and in 2014 (Ali et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Digitalis preparations lower the heart rate and stimulate the contractility of the heart muscle. Beta-blockers are used for treatment of cardiac arrhythmias and may be prescribed as adjunct therapy for heart failure (30)(31)(32). Anti-coagulants such as warfarin, which hinders blood clot formation, and anti-platelet drugs such as acetylsalicylic acid, decrease platelet aggregation.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Retarded eruption of teeth, orthodontic anomalies, enamel hypoplasias and poor oral hygiene due to distraction, caused by the cardiac disease, are common clinical findings among patients with congenital heart disease (CHD) (1). A recent study finds that enamel and dentin of primary teeth of children with CHD have lower amounts of calcium and phosphate in their compound than the average expected in healthy children (2,3).…”
mentioning
confidence: 99%